THE CLINICAL MANIFESTATION OF HIV INFECTION SIMULATING RHEUMATIC DISEASES - E. Yu. Ponomareva; A. A. Shuldyakov; A. V. Anashchenko; A. P. Rebrov (Научно-практическая ревматология)
The symptoms similar to those detected in rheumatic diseases in patients infected with human immunodeficiency virus (HIV) are due to various pathogenetic mechanisms (immune cell imbalance, antibody production, etc.). The occurrence of rheumatic symptoms and syndromes in HIV infection can lead to diagnostic errors and wrong treatment policy (use of immunosuppressive therapy instead of high-dose antiretroviral therapy). The paper describes two clinical cases of HIV infection in the stage of acquired immunodeficiency syndrome (AIDS) in young and middle-aged women, who were misdiagnosed rheumatic diseases at baseline. In the first case, a 34-year-old woman was suspected to have systemic lupus erythematosus before HIV infection diagnosis, whereas the leading clinical syndrome was nephropathy (nephrotic syndrome, hypertension). In the other case, in a 62-year-old woman, the manifestations of the advanced stage of HIV infection at baseline were regarded as mixed connective tissue disease, while the greatest similarity was found in the concurrence of Sjö gren’s syndrome. The paper discusses the reasons for diagnostic difficulties in each case and the specific features of organ damages in comparison with the data available in the literature.